Anemia Iron Deficiency in Pregnancy - Ismatova Malikа Muxiddinovna; Azimova Zilola Sobirovna (Central Asian Journal of Literature, Philosophy and Culture, 2022)
Iron needs increase exponentially during pregnancy to meet the increased demands of the fetoplacental unit, to expand maternal erythrocyte mass, and to compensate for iron loss at delivery. In more than 80% of countries in the world, the prevalence of anemia in pregnancy is > 20% and could be considered a major public health problem. The global prevalence of anemia in pregnancy is estimated to be approximately 41.8%.